ANALISIS MATERI ADAB MEMBACA AL-QUR’AN DAN BERDOA BAHAN AJAR AKIDAH AKHLAK MTS KELAS VII BERDASARKAN RELEVANSI TAKSONOMI BLOOM - Farandika Nanda Pratama; Muhammad Miftah; Khoirun Nafi’ah; Muhammad Rizqy Aulia (Fakultas Tarbiyah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2024)
The research aims to determine the suitability of Akidah Akhlak teaching materials for class VII semester II chapter on the etiquette of reading the Koran and praying based on the perspective of Bloom's Taxonomy in the cognitive, affective, psychomotor and psychology of student development. This research uses a qualitative approach with descriptive analysis of teaching materials. As a result of this study, the researcher stated that the material in the class VII Akidah Akhlak teaching materials, chapter on the manners of reading the Qur'an and praying, was adequate, relevant and fulfilled the cognitive, affective, psychomotor and psychological domains of students' development according to the relevance of Bloom's Taxonomy and was appropriate for the participants. students as learning references. However, researchers found deficiencies in the completeness of teaching materials in the cognitive domain, with the use of lay vocabulary which made it difficult for students to understand in their teens, as well as the low quality of illustrations and a lack of group discussion activities in the psychomotor domain, which of course would affect the quality of the psychological domain. Therefore, the researcher provides several recommendations for improving this teaching material which will be discussed in this article.